Penerapan Sistem Pendukung Keputusan Dengan Menggunakan Metode EDAS Dalam Seleksi Penerimaan Penyiar Radio - Mohammad Aldinugroho Abdullah; Rima Tamara Aldisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
A broadcaster is an individual who is responsible for conveying information, entertainment, and interacting with listeners through radio broadcasts. In the world of radio broadcasting, there are a number of criteria that must be met including education, self-confidence, musical knowledge, vocal quality and communication skills. However, the selection process often faces several challenges, including bias in selection and a lack of transparency and objectivity. Some radio stations still use conventional methods such as direct interviews or written tests, which have proven to be less effective. This is where modern technology and selection methods, such as Decision Support Systems (DSS), can play an important role. SPK is information technology that assists in decision making during the radio announcer selection process, with the aim of increasing the effectiveness and efficiency of decisions. Research using the EDAS (Distance From Average Solution) method has proven that the application of SPK can improve the radio announcer selection process. Radio stations can produce high-quality broadcasters and ensure broadcasts that appeal to listeners. The calculation results using the EDAS method show a value of 1 in the Q1 criterion on behalf of Setyowati Budi, validating the success of the selection process.